Investigation of wrapping ribs onto smooth walls for mid-chord internal cooling passages - McGilvray, M; Gillespie, D; Ryley, J (American Society of Mechanical Engineers, 2014)
Internal cooling passage performance is highly influenced by the geometric features placed on the walls to promote high heat transfer. This paper investigates the effects of wrapping the rib turbulators onto either inter passage wall of a filleted, aspect ratio 1:3 passage. Full passage Nusselt number distributions and friction factor along the passage from stationary experiments are presented as a function of Reynolds number. Accompanying numerical calculations applying the realizable k-ε turbulence model are presented to assess RANS calculations ability to predict heat transfer distribitions. These generally show heat transfer similar trends and distributions. However, average heat transfer levels are underpredicted especially at low Reynolds numbers. Comparisons of the rib geometries with non-wall wrapped configurations are made in terms of both Nusselt number distributions and averaged Nusselt number. As expected, adding passage surface area using ribs results in higher total heat transfer and higher pressure losses, both up to 50% compared to baseline rib configuration. Wrapping the ribs onto the trailing edge passage wall results in similar total heat transfer on the ribbed wall with a smaller associated pressure loss than when the ribs are wrapped onto the leading edge of the passage. Application of different turbulence models (realizable k-ε, k-ω SST and RSM) showed difference in Nusselt number distribution, interrogation of the flow solutions reveal differences in mixing and turbulent kinetic energy production.